(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water is maintained in tall tanks as part of the public water system. Because of a shortage of water or difficulties putting out a fire after an earthquake, the collapse of these water tanks could pose major risks to people. According to draught code Part II of IS 1893:2002, twelve raised circular and H-intake storage tanks with a combined capacity of two lakh litres each would be studied in this study. STAAD Pro V8i is used to conduct a response spectrum analysis of elevated circular and H-shaped water intake tanks in seismic zones II and V. A comparison was made between each collected value for the base shear axial force and lateral displacements. There is a divergence in the H-tank and a negligible variance, according to analysis of a comparison of two water tanks.